TERAPI MALARIA PADA ANAK - Rampengan, Novi H. (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Malaria is still a health problem in Indonesia because it is endemic in considerable parts of Indonesia. According to Riskesdas 2010, the most frequent causes of malaria were P. falciparum (86.4%) and P. vivax (6.9%), with mortality in all age groups increased more than 2 times in 2006-2009 compared to years before. One of the reasons is the increase of malaria parasite resistence to malaria treatment. Therefore, WHO and Ministry of Health in Indonesia recommend that malaria treatment must be by evidence of malaria infection with laboratory tests and malaria medicine must be in combination form to prevent the occurence of resistence. The first line treatment for uncomplicated malaria cases is DHP and AAQ meanwhile the second line is quinine and doxycycline. Moreover, the first line treatment for severe malaria cases is artesunate IV or artemeter IM and the second line is kinine IV.Keywords: plasmodium, malaria, uncomplicated malaria, severe malaria, combination therapyAbstrak: Malaria masih merupakan masalah di Indonesia karena terdapat endemis di sebagian besar wilayah Indonesia. Menurut Riskesdas tahun 2010 penyebab malaria yang tertinggi ialah P. falciparum (86,4%) dan P. vivax (6,9%) dengan angka kematian untuk semua kelompok umur meningkat >2 kali lipat pada tahun 2006-2009 dibandingkan tahun sebelumnya. Salah satu penyebabnya yaitu meningkatnya resistensi parasit malaria terhadap obat-obat malaria sehingga WHO dan Kemkes merekomendasikan bukti laboratorium terinfeksi malaria dan pemberian obat anti malaria diberikan kombinasi untuk mencegah resistensi. Lini I obat untuk terapi malaria tanpa komplikasi yaitu DHP, AAQ dan lini II kinin + doksisiklin, sedangkan lini I obat untuk terapi malaria berat yaitu artesunat IV atau artemeter IM dan lini II kinin IV.Kata kunci: plasmodium, malaria, malaria tanpa komplikasi, malaria berat, terapi kombinasi